Analysis of Promotional Media Strategy for Subsidized Housing Sales Using the Ahp Method in the Startup Property Company Pt Real Estate Teknologi - Iswara, Ririn Agustriana; Sulaeman, Suhendar; Hadi, Lukman (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research analyzes the promotional media strategy for subsidized housing sales using the Analytical Hierarchy Process (AHP) method at the startup property company PT Real Estate Teknologi. The study is motivated by the crucial role of subsidized housing in addressing the needs of low-income communities in Indonesia. The objective is to determine the most effective promotional strategy through social media, digital marketing (Meta Ads), and conventional methods to enhance the visibility and sales of subsidized housing. The AHP method was applied to establish a hierarchy of promotional criteria, including social media platforms, target audience, and cost-effectiveness. The research data were collected through interviews with industry experts, observations, and document analysis. The findings reveal that the use of social media platforms such as Instagram, Facebook, and TikTok, along with digital marketing via Meta Ads, significantly improves brand awareness and sales conversion. This research contributes to the company by providing insights for designing more targeted and efficient promotional strategies. Additionally, the results are expected to help the public gain better access to information about subsidized housing while increasing consumer trust and satisfaction. The recommended strategies from this research can serve as a guideline for stakeholders aiming to optimize their digital promotion efforts.